Higher Sensitivity of Planted Forests' Productivity Than Natural Forests to Droughts in China. Issue 10 (20th October 2021) - Zhong, Ziqian; He, Bin; Chen, Yaning; Yuan, Wenping; Huang, Ling; Guo, Lanlan; Zhang, Yafeng; Xie, Xiaoming
Abstract: Planted forests (PFs) account for about one‐third of the total area of forests in China and make important contributions to carbon sequestration and ecosystem services. Droughts pose a major threat to all forest ecosystems and yet, despite the importance of PFs, there is limited information about their sensitivity to drought and how it compares with that of natural forests (NFs). In this study, satellite‐based vegetation indices were used to investigate and compare the sensitivity of PFs and NFs to drought. We found that PFs' productivity was more sensitive to droughts than NFs, demonstrating a stronger correspondence to interannual variations in drought and a larger decline in productivity under drought conditions than NFs. However, PFs tended to recover more rapidly after drought disturbance than NFs. The observed differences in the sensitivity to droughts may reflect intrinsic differences between PF and NF ecosystems. We also found that the difference between the response of PFs and NFs to drought became less notable as the climate aridity increased, indicating influences from external environmental conditions. The findings from this study highlight the importance of increasing the resistance of PFs to climate change by various management strategies, giving special attention to water availability issues. Plain Language Summary: China's afforestation practices have aroused wide concerns in recent years. Planted forests (PFs) differ from natural forests (NFs) in many aspects, such as age, species richness, plant density, and so on. Many studies have explored the sensitivity of forests to climate change, while few of them have specifically focused on the PFs. In this study, the sensitivities of PFs and NFs to drought have been comprehensively examined and compared over China. We found that PFs demonstrated a higher sensitivity to droughts than NFs, which resulted from the structural and functional differences between PFs and NFs ecosystems. Knowledge from this study is crucial for the understanding of changes of PFs in the context of climate change. Key Points: Planted forests (PFs) were more sensitive to droughts than natural forests (NFs) PFs tended to recover more rapidly after drought disturbance than NFs The differences in the sensitivity to droughts may reflect intrinsic differences between PFs and NFs ecosystems